Introduction to semimicro qualitative analysis - Sorum, Clarence Harvey (Englewood Cliffs, New Jersey : Prentice-Hall, 1977)
The highly useful structure established in the fourth edition of this book, a section on the theory of qualitative analysis and one on the detailed practical aspects of the subject, has been maintained in this edition.
Part 1. The theory of qualitative analysis -- Part 2. Laboratory practice.
Includes index.
Keywords: QUALITATIVE ANALYTICAL CHEMISTRY